A Collaborative Research Review Platform for Enhancing Project Quality in Universities in Zimbabwe - Gotora, Tatenda T.; Nleya, Sindiso M. (My University, 2016)
Software project quality in Zimbabwean universities has greatly depreciated due to exhaustion of many Information Technology (IT)- related topics and an infested reliance on the copy-paste philosophy from past researches online without acknowledgement. Over the years most graduates may possibly have been able to get away with project recycling in fulfilling their IT studies in Institutions of Higher Education. Despite the vast improvements in Information Communication Technologies (ICTs) and a plethora of scholarly research material on the internet, this has had a significant impact on production of novel research by students due to skyrocketing plagiarism cases. This research seeks to analyze the current project reviewing process in universities to unearth the drawbacks and to explore other tested interactive platforms which have been used in some institutions like the ECLIPSE-based platform and CPECAEE platform. By so doing the researchers of this paper will go on to postulate the design model of a web based interactive platform which adopts social networking and virtual school framework. The platform is meant to improve project quality through cultivating a spirit of team work in carrying out research work in universities and help grow the potential for start-up initiatives while students are still at college.
Keywords: Higher Education; Software project quality; Collaboration; Interactive platform; Zimbabwe.